Modified poly(ε-caprolactone) with larvae protein environmentally friendly nanofiber: Assessment of interface properties and characterization - Chin-San Wu; Shan-Shue Wang; Dung-Yi Wu; Wanwen Gu (eXPRESS Polymer Letters, 2024)
The protein from black soldier fly larvae was used as a functional ingredient of a novel green nanofiber. Larvae protein powder (LP) was blended with biodegradable poly(ε-caprolactone) (PCL) and processed in an electrospinning machine using a coaxial feeding/mixing method to produce nanofibers approximately 100–350 nm in diameter. To improve the dispersion and interface bonding of various PCL/LP nanofiber components, a homemade compatibilizer, maleic anhydridegrafted poly(ε-caprolactone) (MPCL), was added to form MPCL/LP nanofibers. The structure, morphology, mechanical properties, water absorption, cytocompatibility, wound healing, and biodegradability of PCL/LP and MPCL/LP nanofiber mats were investigated. The results showed enhanced adhesion in the MPCL/LP nanofiber mats compared to PCL/LP nanofiber mats; additionally, the MPCL/LP nanofibers exhibited increases of approximately 0.7–2.2 MPa in breaking strength and 9.0–22.8 MPa in Young’s modulus. Decomposition tests using a simulated body fluid revealed that the addition of LP enhanced the decomposition rate of both PCL/LP and MPCL/LP nanofiber mats and in vitro protein release. Cell proliferation and migration analysis indicated that PCL, MPCL, and their composites were biocompatible for fibroblast (FB) growth. Biodegradability was tested in a 30 day soil test. When the LP content was 20 wt%, the degradation rate exceeded 50%.